(untitled) (LACCEI, 2024)
The efficiency of an electrocoagulation cell was evaluated by obtaining the optimum operating parameters for the contaminant removal from wastewater coming from the textile industry. A batch-type electrochemical cell was designed with aluminum electrodes and a parallel monopolar configuration type. The Response Surface Methodology with a Rotable Composite Central Design was used to evaluate the treatment time, chloride concentration and voltage for the turbidity and color removal, chemical oxygen demand (COD) and total suspended solids (TSS). The results showed that, during an operation time of 16.5 minutes, with a sodium chloride (NaCl) concentration of 29.8 g/L and applying a voltage of 18 V, it is possible to reduce 96% turbidity, 99% color intensity, 97% COD and 96% TSS. In addition, after the electrocoagulation treatment, an energy consumption and a specific energy consumption required for the treatment of a 3 L wastewater sample was 0.02 kW/h and 6.6 kW/h/m3 , respectively and an efficiency of the aluminum anode with values between 91% and 93%.